2002
DOI: 10.1093/jxb/53.366.103
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitric oxide (NO) production by plant nitrate reductase in vivo and in vitro

Abstract: NO (nitric oxide) production from sunflower plants (Helianthus annuus L.), detached spinach leaves (Spinacia oleracea L.), desalted spinach leaf extracts or commercial maize (Zea mays L.) leaf nitrate reductase (NR, EC 1.6.6.1) was continuously followed as NO emission into the gas phase by chemiluminescence detection, and its response to post-translational NR modulation was examined in vitro and in vivo. NR (purified or in crude extracts) in vitro produced NO at saturating NADH and nitrite concentrations at ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
144
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 38 publications
8
144
1
3
Order By: Relevance
“…Consistent with that, NO AE emission was very strongly increased in clone 271. In previous studies, we have already observed a similar positive correlation between nitrite accumulation and NO AE emission in other plant species (Rockel et al 2002), which is consistent with the original reports by Klepper (1979) on soybean. However, it was surprising that the relative increase in NO AE emission was much higher than the relative increase in the nitrite concentration.…”
Section: No Ae Emission and Nitrite Contentsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with that, NO AE emission was very strongly increased in clone 271. In previous studies, we have already observed a similar positive correlation between nitrite accumulation and NO AE emission in other plant species (Rockel et al 2002), which is consistent with the original reports by Klepper (1979) on soybean. However, it was surprising that the relative increase in NO AE emission was much higher than the relative increase in the nitrite concentration.…”
Section: No Ae Emission and Nitrite Contentsupporting
confidence: 92%
“…This has been traced back to the fact that the dark inactivation of NR requires some time, whereas nitrite reduction by photosynthetic electron transfer stops immediately after light off. This transient nitrite accumulation correlates well with the ''light-off-peak'' of NO AE emission observed in the WT (compare Rockel et al 2002). The absence of the ''light-off-peak'' in the NiRdeficient clone 271 is probably due to the fact that there was always plenty of nitrite present in these plants.…”
Section: No Ae Emission and Nitrite Contentsupporting
confidence: 70%
See 2 more Smart Citations
“…The emission of nitric oxide by plants on a global scale is estimated to be in a range of 2.3 × 10 11 g N per year [23]. NO is considered to be involved in various responses of plants including the growth and defence responses [24,25], although the mechanism of the production of NO in plants is still a subject of intensive investigation [24][25][26][27][28]. Whether NO is directly involved as a redox signal in nitrosative stress, i.e.…”
Section: Introductionmentioning
confidence: 99%